Response of Physiological, Reproductive Function and Yield Traits in Cultivated Chickpea (Cicer arietinum L.) Under Heat Stress - Devi, Poonam; Jha, Uday Chand; Prakash, Vijay; Kumar, Sanjeev; Parida, Swarup Kumar; Paul, Pronob J.; Prasad, P. V. Vara; Sharma, Kamal Dev; Siddique, Kadambot H. M.; Nayyar, Harsh (Frontiers in Plant Science, 2022)
Under global climate change, high-temperature stress is becoming a major threat to crop yields, adversely affecting plant growth and ultimately resulting in significant yield losses in various crops, including chickpea. Thus, identifying crop genotypes with increased heat stress tolerance is becoming a priority for chickpea research. Here, we assessed the response of seven physiological traits and four yield and yield-related traits in 39 chickpea genotypes grown in normal-sown and late-sown environments [to expose plants to heat stress (>32/20°C) at the reproductive stage] for two consecutive years (2017–18 and 2018–19). Significant genetic variability for the tested traits occurred under normal and heat stress conditions in both years. Based on the tested physiological parameters and yield-related traits, GNG2171, GNG1969, GNG1488, PantG186, CSJ515, RSG888, RSG945, RVG202, GNG469 were identified as promising genotypes under heat stress. Further, ten heat-tolerant and ten heat-sensitive lines from the set of 39 genotypes were validated for their heat tolerance (32/20°C from flowering to maturity) in a controlled environment. Of the ten heat-tolerant genotypes, GNG1969, GNG1488, PantG186, RSG888, CSJ315, and GNG1499 exhibited high heat tolerance evidenced by small reductions in pollen viability, pollen germination, and pod set percentages, high seed yield per plant (SYP) and less damage to membranes, photosynthetic ability, leaf water status, and oxidative processes. Thus, GNG1969, GNG1488, PantG186, RSG888, CSJ315, and GNG1499 genotypes could be used as candidate donors for transferring heat tolerance traits to high-yielding heat-sensitive varieties to develop heat-resilient chickpea cultivars.